Green Guide Gaps: Expanding FTC Authority Over Low-Carbon Marketing Claims - Cooke, Perrin (Columbia Journal of Environmental Law, 2019)
Too often, environmentalists view American consumerism and corporate advertising as damaging forces necessarily at odds with conservation and sustainability. With this in mind, many environmental activists have emphasized the basic rejection of consumerism as an essential step towards sustainable consumption. Importantly, however, this over-broad dichotomy often ignores the potentially powerful role that consumer culture can play in achieving environmental objectives. In fact, the early environmental movement also heralded an important shift in American consumerism. Just as leaders in Washington began to recognize growing public interest in the environment, companies across the nation sought to capitalize on consumers' newfound environmentalism. Since that time, environmental marketing has continued to draw on consumers' interest in sustainability and is today a familiar element of the American marketplace. Unfortunately, vindicating concerns expressed by many environmental commentators, many companies have found it cheaper to exaggerate the environmental benefits of their products or obfuscate their environmental harms than to improve the environmental performance of their products. The Federal Trade Commission ("FTC", or "the Commission") has responded to exaggerated environmental performance claims by invoking its authority under § 5 of the Federal Trade Commission Act ("FTC Act," or "the Act") to pursue misleading or deceptive advertising. Unfortunately, the FTC's efforts in this field have not proven particularly successful. This Note examines the most recent development in this ongoing effort: the Commission's 2012 Guides for the Use of Environmental Marketing Claims (Green Guides). The 2012 Green Guides represent the FTC's first attempt to address claims related to two particularly important categories of environmental products: renewable energy and carbon offsets. This Note analyzes the new Guides for these products.